The electoral geography of Poland: between stable spatial structures and their changing interpretations - Zarycki, Thomasz (ERDKUNDE, 2015)
The main goal of the paper is to discuss various interpretations of the heritage created during the so-called ‘partition’ of Poland in the 19th century and the ways of its possible reproduction. This goal will be achieved by analyzing patterns of Poland’s electoral geography, which is known for its considerable stability. After a discussion of the historical background and a summary of the main patterns of the country’s electoral geography, the main types of dominating interpretations of the reproduction of structures, brought about in the Polish space during the period of its partitions in the 19th century, will be discussed. The paper will show how the recent transformation of the Polish political scene, which happened about 2005–2007, affected both the structures of the electoral geography and the dominant ways of its interpretation. As it will be argued, the above mentioned changes have emphasized the role of the East-West differentiation of the Polish space. The rise to prominence of that dimension was also related to the emergence of a number of new interpretations, many of which could be seen as heavily relying on orientalistic stereotypes, including those of the very negative images related to the heritage of the Russian rule. These mainstream interpretations, based on models of opposition between the positive Western “civilization” and the negative Eastern (Russian) “backwardness”, will be confronted with what seems to be a more nuanced view on the basic East-West split of the Polish space. The proposed model will be an attempt to apply the theory of different types of capital by Pierre Bourdieu. In particular, Eastern Poland and its heritage of the Austrian and Russian rule will be presented as more cultural-capital oriented, while Western Poland and its heritage of the Prussian rule - as more economic-capital oriented. In this way the paper will propose a new, more general model of analysis of the spatial longue-durée effects.